Informação ambiental e mudança cultural: a escola em rede - Francisco, Maria Beatriz Lopes (2011)
The present study discusses, from the nature-culture relationship experienced by contemporary societies facing environmental problems, the role of information on the behavior of individuals and the importance of socialization of environmental information when attitudes need changing. Viveiros de Castro and Latour present ways of thinking about nature-culture relationship which are different from those in the western world. The first takes up the proposal of the Amerindian perspectivism and Latour proposes to consider the two simultaneously, giving no special place for humans. Information is then one of the elements which can promote awareness of environmental problems, thus enabling the understanding of the need for new environmental practices. To this end, the socialization of information is seen as a relevant point and in this sense, the educational institution becomes an important part of this study, since some authors understand it as a place to socialize information and knowledge, forming values and attitudes. As the academic institution is not the only source of information that students have access to, its relationship with these other sources of information is questioned, as well as its connection with the actors involved. To implement this work, a field survey with 126 students in two schools was necessary and the dissertation compared.the.data.obtained.